A Study of the Internal Control System in a Public Higher Education Institution in Northeastern Thailand - Krutjan, Jiraluk (Journal for Developing the Social and Community, 2025)
Background and Objectives: Internal control is a vital mechanism that enhances governance and organizational efficiency, especially in public higher education institutions undergoing rapid change. This study aims to assess the effectiveness of internal control based on the COSO framework and examine the impact of each component on organizational performance across various dimensions, using the Balanced Scorecard as the evaluation tool. Research Methodology: This quantitative study employed stratified sampling to collect data from 350 academic and administrative staff. A validated questionnaire was used, with a total reliability score of 0.97. Descriptive statistics (mean and standard deviation), Pearson correlation coefficient, and multiple regression analysis were applied for data analysis. Results: The model explains 49.1% of the variance in organizational performance (R² = 0.491, p < 0.001). Significant predictors include risk assessment (β = 0.357, p < 0.001), control activities (β = 0.383, p < 0.001), control environment (β = 0.122, p = 0.041), and communication (β = 0.195, p = 0.003). Conversely, monitoring activities showed a negative impact on performance (β = -0.314, p < 0.001). The study also proposes internal control development strategies aligned with strategic goals and sustainable operations. Conclusion: Internal control aligned with the COSO framework and integrated with the Balanced Scorecard can significantly enhance organizational performance in public higher education institutions, particularly under governance contexts that require transparency, efficiency, and strategic alignment.